Gastric transcatheter chemoembolization can resolve advanced gastric cancer presenting with obstruction - Peng, Dong; Zhang, Bin; Yuan, Chao; Tong, Yue; Zhang, Wei (Frontiers in Surgery, 2022)
Background Gastric transcatheter chemoembolization (GTC) is an interventional minimal invasive method, which has never been mentioned in the previous literature for advanced gastric cancer with obstruction. The purpose of this study was to evaluate its safety and efficacy in treating advanced gastric cancer with obstruction. Methods Advanced gastric cancer patients with obstruction who underwent GTC were retrospectively analysed from June 2017 to January 2020. Baseline information, peri-intervention data, and post-intervention follow-up information were collected. Clinical data obtained before and after the GTC were compared, and the survival of all patients was analysed. Result Forty-Two patients were included in this study. 42 (100%) patients achieved technical success, and 22 (52.4%) achieved clinical success. The median time of the GTC was 83 (30.0-180.0) minutes, and the median time of hospitalization after GTC was 3 (1-6) days. One patient experienced abdominal pain during and after GTC. Twenty (47.6%) of the 42 patients underwent gastrectomy after intervention. The pre-intervention gastric outlet obstruction scoring system(GOOSS) was 1 (0-1) and the post-intervention GOOSS was 2 (0-3) (p=0.000<0.05). The median follow-up time was 9.5 (3-35) months, and the overall survival time was 14 months. In the univariate survival analysis, a significant difference was observed between patients who did or did not undergo radical gastrectomy after GTC (p = 0.014<0.05). Conclusions GTC is a safe and effective treatment, and furthermore, it could be an alternative method in treating advanced gastric cancer with obstruction.